Bioprospecting for Genes Encoding Hydrocarbon-Degrading Enzymes from Metagenomic Samples Isolated from Northern Adriatic Sea Sediments - Gacesa, Ranko; Baranasic, Damir; Starcevic, Antonio; Diminic, Janko; Korlević, Marino; Najdek, Mirjana; Blažina, Marijana; Oršolić, Davor; Kolesarić, Domagoj; Long, Paul F.; Cullum, John; Hranueli, Daslav; et al. (Food technology and biotechnology, 2018)
Three metagenomic libraries were constructed using surface sediment samples from the northern Adriatic Sea. Two of the samples were taken from a highly polluted and an unpolluted site respectively. The third sample from a polluted site had been enriched using crude oil. The results of the metagenome analyses were incorporated in the REDPET relational database (http://redpet.bioinfo.pbf.hr/REDPET), which was generated using the previously developed MEGGASENSE platform. The database includes taxonomic data to allow the assessment of the biodiversity of metagenomic libraries and a general functional analysis of genes using hidden Markov model (HMM) profiles based on the KEGG database. A set of 22 specialised HMM profiles was developed to detect putative genes for hydrocarbon-degrading enzymes. Use of these profiles showed that the metagenomic library generated after selection on crude oil had enriched genes for aerobic -alkane degradation. The use of this system for bioprospecting was exemplified using potential and genes from this library.